Nosocomial Outbreak of Enterobacter gergoviae bacteraemia in a neonatal intensive care unit - Ganeswire, R.; Thong, Kwai Lin; Puthucheary, S.D. (2003)
A nosocomial outbreak of bacteraemia, caused by Enterobacter gergoviae infected 11 babies, nine of whom were premature, and was investigated in the neonatal intensive care unit (NICU) of a general hospital in Johor Bahru, Malaysia. The strain that was isolated from the babies was also isolated from the dextrose saline used for the dilution of parenteral antibiotics and from the hands of a healthcare worker on duty in the nursery. Pulsed-field gel electrophoresis (PFGE) of XbaI-digested chromosomal DNA confirmed a possible cross-contamination of parenteral dextrose saline and the healthcare worker. Prompt and effective control measures were initiated within NICU and the nosocomial infection of E. gergoviae was brought to an abrupt end. To the best of our knowledge, this is the first documented outbreak of E.gergoviae in the NICU in a hospital in the state of Johor, Malaysia. (C) 2002 The Hospital Infection Society.